Odpowiedzi

2010-02-04T21:35:04+01:00
6+(-4)+(-10)=6-4-10=-8
-4-(-9)-3=-4+9-3=2
-16+7-28=-37
4,3-7,4+1,1=-2
(-6,2)+1,6-(-2,3)=-2,3
7,8-5,4-12,1=-9,7
(-2,1)+ulamek(jedna piata)-3=-4,9
2010-02-04T21:35:28+01:00
Oblicz:
6+(-4)+(-10)=6-4-10=-8
-4-(-9)-3=-4+9-3=9-7=2
-16+7-28=7-44=-37
4,3-7,4+1,1=5,4-7,4=-2
(-6,2)+1,6-(-2,3)=-6,2+1,6+2,3=-6,2+3,9=-2,3
7,8-5,4-12,1=7,8-17,5=-9,7
(-2,1)+ulamek(jedna piata)-3=0,2-5,1=-4,9
ulamek jedna piąta 0,2
2010-02-04T21:36:50+01:00
6+(-4)+(-10)=2+(-10)=-8
-4-(-9)-3=(-13)+3=(-10)
-16+7-28=-9-28=37
4,3-7,4+1,11=5,4-7,4=(-2)
(-6,2)+1,6-(-2,3)=(-4,6)-(-2,3)=(-2,3)
7,8-5,4-12,1=25,3
(-2,1)+ulamek(jedna piata)-3=(-2,1)+0,2-3=(-1,9)-3=-4,9